Mechanistic insights from metagenomics into the early-stage quality improvement of licorice under partial replacement of chemical by organic fertilizers - Xiao, Jiancai; Gao, Pengchao; Lai, Kunyang; Binbin, Yan; Wang, Sheng; Zhao, Yuping; Wan, Xiufu; Lyu, Chaogeng; Kang, Chuanzhi; Guo, Lanping; Zhang, Yan (Frontiers in Plant Science, 2025)
Substituting chemical fertilizers with organic alternatives has gained increasing attention for its potential to enhance crop yield, quality, and soil health. In the early stages of licorice cultivation, the short-term effects of organic fertilization on microbial community dynamics, soil properties, and bioactive compound accumulation remain insufficiently understood. A metagenomic approach was applied to analyze microbial compositions in both bulk and rhizosphere soils under different fertilization treatments. Results showed that organic fertilization significantly increased licorice yield and the accumulation of bioactive compounds compared to chemical fertilization. Full organic substitution improved soil nutrient content, organic matter, and carbon levels while reducing enzyme activities such as urease and protease. Additionally, organic fertilization promoted bacterial diversity, with notable increases in Actinobacteria and fungal taxa such as Ascomycota and Basidiomycota. Correlations between soil microbial communities, enzyme activity, and secondary metabolite synthesis—particularly glycyrrhizic acid—were observed. These findings suggest that organic fertilization fosters microbial diversity and soil health, ultimately benefiting licorice production and quality in the early stages of cultivation while contributing to sustainable agricultural practices.